Chemistry and antigerminative activity of essential oils and monoterpenoids from mediterranean plants - de Martino, Laura; Mancini, Emilia; Marandino, Aurelio; de Almeida, Luiz Fernando Rolim [UNESP]; de Feo, Vincenzo (Bentham Science Publishers, 2012)
The Mediterranean flora is characterized by the abundance of aromatic plants. The feature differentiating these plants from all others, in spite of the fact that they belong to many different families, is the production of chemically related secondary compounds, the low molecular weight and volatile isoprenoids. This remarkable presence of aromatic species is important in determining the phytotoxic potential within this ecosystem. Such plants make a significant contribution to phryganic Mediterranean ecosystems both in terms of species number and biomass. Thus, the essential oils play an important role in this ecological context. Mediating various processes in the frame of an ecosystem, they become indirectly beneficial to the plants, considering their involvement in processes of adaptative character in Mediterranean ecosystem. For this reason, our research group carried out a series of studies on the possible phytotoxic properties of aromatic plants that, being rich in active principles, are considered a primary source of potential allelochemicals.The focus of this overview is direct to have an overall idea about the chemistry and antigerminative activity of essential oils of some Mediterranean aromatic plants and their main constituents.
Keywords: Antigerminative activity; Aromatic plants; Chemistry; Essential oils; Mediterranean flora; Monoterpenes